Competency-Based Curriculum: Linking Theory and Practice - elaheh sharbaf; hosein H. Karimi Moonaghi; ali emadzadeh; soleyman ahmady (Babol University of Medical Sciences, 2022)
Background and objective: Most higher education curricula do not provide the competencies graduates need in the occupational fields, resulting in waste of money and lower effectiveness while increasing the number of unemployed graduates. Competency-based education is an innovative educational model that can solve such problems and lead education activists to design competency-based curricula. Therefore, this study aimed to identify the necessary competencies in the master's curriculum of medical education. Methods: Byham and Moyer's methodology was used to determine the competency model in this research. Accordingly, the relevant literature and 37 similar curricula were primarily reviewed, after which interviews were conducted with 17 members of the medical education evaluation board and professors and 15 graduates working in this field. An initial list of competencies was prepared in the third step, which were then validated using SPSS 25 to provide the final list of competencies of medical education graduates in the last stage. Finding: The 61 final competencies obtained in the study were divided into 5 areas of education, evaluation, research, management, and professionalism and 26 sub-areas.  Conclusion: The analysis of the obtained competencies can provide policy makers and medical education proofers with deeper insights and knowledge to employ when assessing educational needs, setting goals, designing content, planning curriculum, performing educational assessment and evaluation and developing curriculum.